2021
DOI: 10.1136/tobaccocontrol-2021-056742
|View full text |Cite
|
Sign up to set email alerts
|

Using place-based characteristics to inform FDA tobacco sales inspections: results from a multilevel propensity score model

Abstract: BackgroundConducting routine inspections for compliance with age-of-sale laws is essential to reducing underage access to tobacco. We seek to develop a multilevel propensity score model (PSM) to predict retail violation of sales to minors (RVSM).MethodsThe Food and Drug Administration compliance check of tobacco retailers with minor-involved inspections from 2015 to 2019 (n=683 741) was linked with multilevel data for demographics and policies. Generalised estimating equation was used to develop the PSM using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Impacting tobacco retail more broadly, federal legislation raised the minimum legal sales age for e-cigarette sales from 18 to 21 (i.e., Tobacco 21 [T21]) in December 2019 [ 15 ]. Despite evidence of the public health benefits from T21 (e.g., youth prevention) [ 16 , 17 ], and the potential to increase awareness and support for tobacco control efforts among retailers and consumers [ 18 ], there are high noncompliance rates in some states [ 19 , 20 ], noncompliance may be underestimated [ 19 ], and gaps in FDA enforcement protocols have been identified [ 20 , 21 ]. In addition, there is growing concern about noncompliance rates for e-cigarette sales, especially among tobacco specialty shops [ 22 , 23 ], and online retailers [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impacting tobacco retail more broadly, federal legislation raised the minimum legal sales age for e-cigarette sales from 18 to 21 (i.e., Tobacco 21 [T21]) in December 2019 [ 15 ]. Despite evidence of the public health benefits from T21 (e.g., youth prevention) [ 16 , 17 ], and the potential to increase awareness and support for tobacco control efforts among retailers and consumers [ 18 ], there are high noncompliance rates in some states [ 19 , 20 ], noncompliance may be underestimated [ 19 ], and gaps in FDA enforcement protocols have been identified [ 20 , 21 ]. In addition, there is growing concern about noncompliance rates for e-cigarette sales, especially among tobacco specialty shops [ 22 , 23 ], and online retailers [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multilevel modeling also examined the associations between relevant state-level policies (e.g., T21, e-cigarette flavor restrictions, non-medical cannabis sales) and participant experiences of vape shop practices. Notably, findings from these analyses indicated that state T21 was not significantly associated with age verification upon entering vape shops or purchasing e-cigarettes at vape shops among participants under age 27, suggesting potential variations in the implementation and enforcement of T21 laws across states [ 23 , 24 ]. This may also be partially explained by the fact that state T21 laws varied in terms of guidance on the minimum age for verification [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the US government implemented the federal T21 law on 20 December 2019 [ 21 ], and prior to then, many US states and localities had implemented T21 laws. Although federal T21 declares no exemption of the minimum age requirement [ 21 ], there are gaps in enforcement protocols [ 22 , 23 ] and underestimates of noncompliance [ 24 ]. Particularly relevant to the current study, T21 implementation varies in relation to whether states previously had a T21 law in place [ 23 , 24 ] and whether state laws previously had required age verification for consumers under 27 years old (as the federal law requires) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating compliance with policies and effects on tobacco use is a major focus of this e-issue, with 9 of 17 studies examining minimum legal sales age (MLSA), [22][23][24][25] price and flavour restrictions, [26][27][28] or tobacco sales bans. 29 30…”
Section: Retail Policy Enforcement and Evaluationmentioning
confidence: 99%